KEMENANGAN DONALD TRUMP SEBAGAI PRESIDEN AMERIKA SERIKAT KE-45 MELALUI ANALISIS KONSTRUKSI KLAUSA RELATIF BAHASA INGGRIS DAN BAHASA INDONESIA SECARA SEMANTIS - Aini, Aldila Arin; Bastiar, Islamiah; Sumarlam, S. (PRASASTI: Journal of Linguistics, 2018)
This research aims (1) to comprehend the relative construction of English and Indonesia language on some texts relating to Donald Trump is elected as the 45th President of USA in 2016 semantically, and (2) to describe the analysis of relative constructive clauses between English and Indonesia language semantically. The research method is descriptive qualitative. Meanwhile, method of collecting data is agih method and the techniques are substitution, expand, interuption, and mutation. Based on the texts relating to Donald Trump is elected as the President of USA in 2016, it is found that the analysis of relative constructive clause of English and Indonesia language is based on the use of conjunction. In Indonesia language texts, there is one conjuction, namely: â€œyangâ€, meanwhile in English language texts, there are five conjuctions, namely: â€œwho, whom, which, whose, and thatâ€. If it is viewed from its semantics adjacent, relative clause can be divided into two sections based on its orthographics, namely: (1) restrictive relative clause which refers to the explained antecedent or as the integral unity from antecedent and unmarked by comma, and (2) non-restrictive relative clause as the additional information from antecedent explained and marked by comma.